Esejistično delo Helene Koder - Vollmaier Lubej, Janja (Slavia Centralis, 2025)
The Essayistic Work of Helena Koder. The article presents the essayistic work of the renowned Slovenian essayist Helena Koder, who won the Rožanc Award for her book Krošnja z neznanimi sadeži (Tree Crown Bearing Unknown Fruit, 2024). Compared to other contemporary essayists Helena Koder’s texts are considered to be reflective essays with poetic elements, as she deals with central themes like art, culture and language. Her essays are both discursive and interpretive, while also containing side stories and dreams. The structure of her essays is carefully thought out, as each essay contains a photograph linked to its content, followed by an appendix at the end functioning as a supplement to the essay.